Theoretical Insights on Financial Sustainability Regulations in the European Union - Kubiliūtė, Dalia (Teisė, 2025)
This article explores the legal challenges of the regulation of financial service providers’ activities in the context of climate change. The European Union’s commitment to sustainability, first embodied in the European Green Deal, has led to increased compliance challenges for financial institutions, including new rules on Environmental, Social, and Governance (ESG) disclosures. While these legal regulations aim to mitigate climate change risks, they raise questions about the changing paradigm, particularly regarding the freedom of economic activity and the proportionality of such new legal requirements. This article examines how legal regulations pertaining to sustainability are embedded in the legal juncture, in terms of a balance between long-term societal benefits and the compliance burdens on financial service providers. It also examines recent innovations in legal structures, such as the Sustainable Finance Disclosure Regulation (SFDR) and the Corporate Sustainability Reporting Directive (CSRD), and how these changes impact the balance between profitability and compliance for financial service providers. The analysis highlights the need for ESG compliance, while emphasizing proportionality and state support, in order to ensure financial stability and the continued viability of the financial sector in the face of changing regulatory requirements.
Keywords: Climate change; financial service provider; legal regulatory compliance; sustainability